Estudio isotópico del acuífero de Lima - Plata, A. (1993)
Filtrations from Rimac and Blanco rivers and Graton Tunnel (on the Rimac basin, 80 km from Lima. and 2500 m sea level) were studied using artificial tracers and superficial water analysis. Graton tunnel has a 3-5 m3/s volume. Domestic and industrial demand of Lima (7 million inhabitants) is 22 m3/s. Preliminary results suggest that Graton tunnel filtrations do not originate on Rimac or Blanco rivers, but in regions at 4600 m sea level. Detected tritium suggests that water filtrated in Graton tunnel is modern.